GAMBARAN PERFORMA INSTRUKTUR SKILL LAB PROGRAM STUDI KEDOKTERAN DI FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI - Panggabean, Agnesia Feronika; Ayu Safira, Nyimas Natasha (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2016)
Abtract Background: Skill lab is an important place for students to learn and prepare themselves to acquire a doctor's competence. Skills learning is different from cognitive learning, in which students are able to learn independently. In the skills learning, they need guidance and supervision from instructor. The performance of a skill lab instructor is very influential on the achievement of skill lab learning objectives. The purpose of this study is to describe the performance of the skill lab instructor of Program Studi Kedokteran at FKIK UNJA, on teaching skill, interpersonal and communication skills category as well as the condition / clinical skill training strategy based on the perception of students using a questionnaire. Methods: This study employs quantitative descriptive research. This research was conducted in June 2015. The respondents were 215 students of Medical Study Program of FKIK UNJA 2012 and 2013. The instrument that was used in this research is a questionnaire entitled "Instrument for Evaluating Clinical Skills Teacher's lab didactical Performance". Data were analyzed using a computer program. Results: Didactil skills, interpersonal and communication skills of skill lab instructor in Program Studi Kedokteran FKIK UNJA is rated as good by students, with the percentage of good to excellent category amounted for 94.4%. Performance conditions / clinical skill training strategy is rated good by the students with the percentage of 80.5%. Conclusion: In general, the performance of skill lab instructor in Program Studi Kedokteran in FKIK UNJA is good based on the perception of students. Keywords: skill lab, clinical skills, instructor, performance